2019
DOI: 10.1002/ejoc.201801602
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Access to (E/Z)‐α‐Fluorovinyl Phosphorus Compounds from gem‐Difluorostyrenes

Abstract: A facile and efficient method for the synthesis of (E/Z)‐α‐fluorovinyl phosphorus compounds from gem‐difluorostyrenes with diphenylphosphine oxide/dialkyl phosphate and DBU at room temperature was developed. A series of 1‐fluorovinyl phosphine oxides/phosphonates were obtained with moderate to excellent yields in these reactions. Additionally, most isomers (E/Z type) of the target compounds could be easily separated and purified by column chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…Among the established protocols, C—H activation coupled C—F bond functionalization is of particular interest because of the outstanding efficiency and broad substrate scope. Our group recently reported that merging C—H and C—F bonds activation gave rise to defluorinative arylation products under mild conditions . This reaction paradigm of coupling gem ‐difluoroalkenes with Ar—H species was subsequently followed by a series of C(sp 2 )—H/C(sp 3 )—H activation engaged defluorinative arylation/alkylation reported by the groups of Li, Ackermann, Fu, Wang and others (Scheme b) .…”
Section: Background and Originality Contentmentioning
confidence: 89%
“…Among the established protocols, C—H activation coupled C—F bond functionalization is of particular interest because of the outstanding efficiency and broad substrate scope. Our group recently reported that merging C—H and C—F bonds activation gave rise to defluorinative arylation products under mild conditions . This reaction paradigm of coupling gem ‐difluoroalkenes with Ar—H species was subsequently followed by a series of C(sp 2 )—H/C(sp 3 )—H activation engaged defluorinative arylation/alkylation reported by the groups of Li, Ackermann, Fu, Wang and others (Scheme b) .…”
Section: Background and Originality Contentmentioning
confidence: 89%
“…In 2019, Hao, Yang and coworkers developed a new reaction in mild conditions using DBU in DMF at room temperature to prepare α-fluorovinyl phosphine oxides, from gem-difluoroalkenes and diphenylphosphine oxide (18 examples), dialkylphosphine oxide (1 example) or dimethylphosphite (2 examples) (Scheme 47). [73] They obtained moderate to high yields albeit with low E/Z selectivity. Nevertheless, most of the E and Z compounds could be separated by column chromatography.…”
Section: α-Fluorovinyl Phosphine Oxidesmentioning
confidence: 99%
“…Gas chromatographic analyses were performed on a Shimadzu GC 2030 gas chromatography instrument with a FID detector, and adamantane was added as an internal standard. 1 H, 13 C{ 1 H}, and 19 F NMR data were recorded with Bruker AVANCE NEO (600 MHz) and Agilent DD2 600 (600 MHz) spectrometers with tetramethylsilane as an internal standard. All chemical shifts (δ) are reported in parts per million and coupling constants (J) in hertz.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In particular, selective cleavage and transformation of one C–F bond gem -difluoroalkene provides an attractive alternative to functionalized monofluoroalkenes that can be used as peptide bond isosteres in drug discovery . The difluoromethylene carbon of gem -difluoroalkenes is susceptible to nucleophilic attack, such as various carbon-, oxygen-, nitrogen-, boron-, silicon-, sulfur-, and phosphine-centered nucleophilic intermediates. Very recently, we disclosed the visible-light-promoted E -selective synthesis of α-fluoro-β-arylalkenyl sulfides with gem -difluoroalkenes and sodium sulfinates via a deoxygenation/isomerization process .…”
mentioning
confidence: 99%